FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN PROPERTY DAN REALESTATE YANG TERDAFTAR DI BEI PERIODE TAHUN 2012- 2014 - Hendra Dwipana Aji, 15.05.62.0020; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2017)
This study is a research that analyzes the factors that affect audit delay on property and real estate companies listed on the BEI period 2012 - 2014. In this research, the method used in sampling is purposive sampling method. Dependent variable in this research is audit delay, while the independent variable is company size, audit committee, profitability of company, solvability, and reputation of auditor. The data analysis tool used is descriptive statistics and data analysis method is multiple linear regression with F test and t test. The result of partial research (t test) found that solvability have significant negative effect to audit delay, auditors reputation has a significant positive effect on audit delay, firm size has no significant effect on audit delay, audit committee has no significant effect on audit delay and profitability has no significant effect on audit delay.Keywords: Audit Delay, Company Size, Audit Committee, Corporate Profitability, Solvency, and Auditorâs Reputation